An improved scheme for enhancing the ride-through capability of grid-connected photovoltaic systems towards meeting the recent grid codes requirements - Haidar, A.M.A.; Julai, N. (Elsevier B.V., 2019)
With the increasing number of solar PV systems, the future grid-connected converters should provide a full range of services. Such requirements make the operators of the distribution system modify the current grid codes to ensure the security of the power grid and enhance the Low Voltage Ride-Through (LVRT) capability of renewable energy resources (RER). Nowadays, in many countries, the smart grid is standardized, and thus, the development of control strategies for a grid-connected PV system is crucial, particularly with the high level of PV penetration. Initially, the paper reviews the grid codes for LVRT capability of grid-connected solar PV systems. Furthermore, the paper proposes an improved protection control strategy for the DC link of grid-connected PV system with reactive power support to enhance the LVRT during grid faults. The test results presented in this paper have vindicated the effectiveness of the proposed approach.